«La directura curaschusa ....» oder Die sprachliche Gleichberechtigung im Rätoromanischen - Dazzi Gross, Anna-Alice; Caduff, Ester (My University, 2000)
Linguistic equality in Romansh has no doubt received more attention since the 1980s when the new standard Romansh language (Rumantsch Grischun) was created. Today, however, the discussion has slowed down a bit. Given the fact that a great amount of Romansh texts are translations from German, linguistic equality in Romansh texts depends to a high degree on the German original. If the German original text strives for linguistic equality, the Romansh translation will adopt it as well. There is often a great discussion whether a sexist German text should be changed into a non-sexist or less sexist Romansh translation. Romansh translators time and again point out linguistic inequalities to their clients. Sometimes this even results in a subsequent change of the German text. Nevertheless, careful listeners, watchers and readers almost daily meet sexist usage of language in German as well as in Romansh.